PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 LENGAYANG - Fanesa, Dira Yuni; Mukhni, Mukhni (Pendidikan Matematika, 2013)
This research has the background that the progression of studentsâ concept comrehensions and their mathematical concept comprehensions are still low. The purposes of this research are to know: 1) the progression of concept comprehension of VIII-grade students of SMPN 2 Lengayang by applying the active learning strategy with ICM type in mathematical learning in an experimental class, and 2)Â  whether the studentsâ mathematical concept comprehension by applying the active learning strategy with ICM type is better than that by using the conventional learning for the VIII-grade students of SMPN 2 Lengayang.This is an experimental research. The population in this research is the VIII-grade students, who were registered in the year 2013/2014. The selected samples were VIIIa-class as an experimental class and VIIIb-class as control.Â  The instrument used in this research is tests of concept comprehension in the form of essay with reliability of 0.594.Based on the results of data analysis on the studentsâ mathematical concept comprehension for both sample classes, it is obtained that the average concept comprehension for the experimental class is 74.24 and for the control class 60.62. The results of hypothesis tests show that P-value is 0.003 on the real level ofÂ Â Â Â Â Â Â  Î± = 0.05, and because P-value < Î±, H0 is rejected and H1 is accepted. Then, it can be concluded that the studentsâ mathematical concept comprehension by applying the active learning strategy with ICM type is better than that by using the conventional one for the VIII-grade students of SMPN 2 Lengayang.